Mathematical modeling of trajectories construction, movement of the gripping device of a collaborative robot - Nevliudov, Igor; Omarov, Murad; Yevsieiev, Vladyslav; Maksymova, Svitlana; Jabrayilzade, Elgun (Національний технічний університет "Харківський політехнічний інститут", 2026)
The object of the study is the process of constructing and analyzing the trajectories of the gripping device of a collaborative robot-manipulator under spatial constraints and the presence of obstacles in a dynamic environment. The subject of the study is mathematical models, algorithmic and software for modeling the optimal motion of the manipulator end effector taking into account kinematic, dynamic and energy constraints. The aim of the research is to construct trajectories of the collaborative robot's gripping device, taking into account constraints and optimal control actions in continuous time, which ensure the construction of trajectories with minimal energy consumption, compliance with given spatial constraints, and avoidance of collisions with obstacles. The research methodology is based on the application of the Pontryagin maximum principle to form the conditions for optimal control and the construction of a system of differential equations with boundary conditions. A special cost functional has been developed to quantify energy consumption and take into account penalties for approaching prohibited zones. The numerical solution of the problem was implemented using the Euler method, and the optimization of the trajectory parameters with fixed final effector coordinates was implemented using the least squares method with constraints. The Python programming language and the Matplotlib library were used to visualize the results. As a result of the study, optimal trajectories of the gripping device were obtained, which ensure collision avoidance, compliance with spatial constraints, and reduced energy consumption when reaching the specified final effector positions. The simulation confirmed the effectiveness of the developed method and its resistance to changes in environmental parameters. The conclusions of the study indicate that the proposed approach allows for a comprehensive solution to the problem of planning the movement of collaborative robots in the optimal control mode taking into account constraints. The results obtained can be applied in Industry 5.0 production systems, robotic service complexes, automated warehouse systems, and robots that interact with humans in a limited space.

Об’єктом дослідження є процес побудови та аналізу траєкторій руху захоплювального пристрою колаборативного робота-маніпулятора в умовах просторових обмежень та наявності перешкод у динамічному середовищі. Предметом дослідження є математичні моделі, алгоритмічне та програмне забезпечення для моделювання оптимального руху кінцевого ефектора маніпулятора з урахуванням кінематичних, динамічних та енергетичних обмежень. Метою роботи побудова траєкторій руху захватного пристрою колаборативного робота з урахуванням обмежень та оптимальних керуючих дій у безперервному часі, що забезпечують побудову траєкторій із мінімальними енерговитратами, дотриманням заданих просторових обмежень та уникненням зіткнень із перешкодами. Методологія дослідження ґрунтується на застосуванні принципу максимуму Понтрягіна для формування умов оптимального керування та побудови системи диференційних рівнянь із граничними умовами. Для кількісної оцінки енерговитрат та врахування штрафних санкцій за наближення до заборонених зон розроблено спеціальний функціонал вартості. Чисельне розв’язання задачі реалізовано методом Ейлера, а оптимізацію параметрів траєкторії з фіксованими кінцевими координатами ефектора — методом найменших квадратів із обмеженнями. Для візуалізації результатів використано мову програмування Python та бібліотеку Matplotlib. У результаті дослідження отримано оптимальні траєкторії руху захоплювального пристрою, які забезпечують уникнення зіткнень, відповідність просторовим обмеженням та зменшення енергоспоживання при досягненні заданих кінцевих положень ефектора. Моделювання підтвердило ефективність розробленої методики та її стійкість до зміни параметрів середовища. Висновки дослідження свідчать, що запропонований підхід дозволяє комплексно вирішувати завдання планування руху колаборативних роботів у режимі оптимального керування з урахуванням обмежень. Отримані результати можуть бути застосовані у виробничих системах Індустрії 5.0, роботизованих сервісних комплексах, автоматизованих складських системах та роботах, що взаємодіють із людиною в обмеженому просторі.
Математичне моделювання побудови траєкторій руху захватного пристрою колаборативного робота
Keywords: collaborative robot; robot manipulator; trajectory of the roc; gripping device; mathematical modeling; Pontryagin's maximum principle; колаборативний робот; робот-маніпулятор; траєкторія руху робота; захоплювальний пристрій; математичне моделювання; принцип максимуму Понтрягіна